Conflicting Religious Identities: Blaspheming Islam and the Future of Democracy in Indonesia - Hamdi, Saipul (Pascasarjana IAIN Pontianak, 2017)
The paper explores the phenomena of conflicting religious identities among Indonesian politicians in Jakarta’s regional election (pilkada) in 2017. The 2017 most dramatized Jakarta regional election has been seen as a very important political phenomenon in recent time as it revealed the conflicting social-political identity construction across religious and ethnic groups in the region. This work attempts to provide explanation from the perspective of religious studies on the roles of religious identities in the political realm as well as religious and political symbols as tools to achieve political supports. The case of Ahok mentioning one of the Quranic verses of al-Maidah 51 in Kepulauan Seribu exposes the fundamental question of wheter it is apart of blaspheming Islam and insulting ulama. It also shows how the Islamist groups respond to it by using the case of the politicizing al-Maidah 51 to reduce Ahok electability and disqualify him from political contestation by accusing him to blaspheme Islam. The complexity of applying Quranic texts to the modern political platform brings this article to outline how Muslim scholars interpret all-Maidah 51 and how they situate the text into the context of modern politics in Indonesia as well as how it influences the future of Indonesian democracy.